Purification of Laboratory Chemicals (5th Edition) - Armarego, Wilfred L.F. (Butterworth-Heinemann, 2011)
Outlines for chemists, biochemists and other scientists procedures and processes for purifying over 4000 organic and 750 inorganic and organometallic commercially available chemicals.